Generation Z Marriage Delay Drivers and Islamic Law Tensions - Waris, Abdul; Ishaq, Ishaq; Faisol, Muhammad (Academia Open, 2026)
General Background Marriage is a central institution in Islamic teaching and social order, yet contemporary youth increasingly reconsider its timing within changing socio-cultural contexts. Specific Background This study examines the phenomenon of delayed marriage among Generation Z through a socio-legal lens that integrates sociological analysis with Islamic family law perspectives. Knowledge Gap Prior discussions have not sufficiently bridged empirical social behavior of youth with normative Islamic legal frameworks, particularly in relation to evolving values shaped by modernization and digital culture. Aims The study aims to identify key social factors underlying marriage postponement among Generation Z and assess their relevance to Islamic family law principles. Results Findings reveal four dominant drivers: economic constraints, educational and career priorities, social media exposure, and environmental as well as lifestyle factors. Economic considerations and digital influences demonstrate notable tension with Islamic legal norms that prioritize timely marriage, while educational aspirations show partial alignment when balanced with religious obligations. Novelty The research introduces an interdisciplinary socio-legal approach combining empirical insights and normative analysis, offering a comprehensive understanding of youth decision-making within Islamic legal discourse. Implications The study suggests the need for adaptive interpretations of Islamic family law that remain responsive to social transformation while preserving core religious values, supporting policy and educational initiatives addressing generational shifts in marital perspectives. Highlights: Financial readiness, academic pursuit, and digital exposure shape postponement decisions. Normative religious expectations intersect with shifting youth value orientations. Interdisciplinary socio-legal framing clarifies contemporary marital perceptions. Keywords: Postponing, Marriage, Gen Z Perceptions, Sociological Analysis, Islamic Family Law